Presentation: Church and Independence - Cavieres Figueroa, Eduardo (2020)
The dossier that is presented in the following pages, entitled "The Church and Independence in Latin America, particularly in the cases of Chile and Peru (Arequipa)", emerged at a working meeting held at the Pontificia Universidad Católica de Valparaíso in October 2018. The said session - colloquium - was the result of a previous agreement between the Ibero-American Studies Program (PEI * sur), of the said university and the Center for Peruvian Studies (CEP) of the Catholic University of San Pablo, Arequipa, and therefore had the presence of academics from both houses.